ANALISIS PENGARUH DISKON, PROMOSI, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI SHOPEE PADA MAHASISWA UNIVERSITAS PENDIDIKAN MANDALIKA PRODI MANAJEMEN ANGKATAN 2021 - Sami`un, Sami`un; Hana, Fermatika Oktavia (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This research was conducted to find out how much influence Discounts, Promotionsand Consumer Trust haveon Purchase Decisions for Shopee Application Usersin the Mandalika University Of Education student circle. This study uses multiple linear regression analysis method to verify the effect of Discounts, Promotions and Consumer Confidence thataffect the decisions of Mandalika University Of Education students in purchasing products onthe Shopee application. The data used are primary data obtained from the distribution of questionnaires with 60 respondents. The results of this study indicate that there is a significant positive effect of discounts on purchasing decisions for Mandalika University OfEducation students who use the Shopee application. There is a significant positive effect ofpromotion on purchasing decisions for Mandalika University Of Education students who use the Shopee application. There is a significant positive effect of Consumer Trust on purchasing decisions for Mandalika University Of Education students who use the Shopeeapplication. There is a simultaneous significant positive effect of discounts, promotions and consumer confidence on purchasing decisions for Mandalika University Of Educationn students who usethe Shopee applicationKeywords: Discount, Promotion, Consumer Confidence, e-commerce